PENGARUH LITERASI KEUANGAN DAN PENGGUNAAN FINANSIAL TEKNOLOGI TERHADAP PENGELOLAAN KEUANGAN INDIVIDU SISWA SMK CENDIKIA PASEH - Auliya, Astri Nurul; Devi, Rizca Puspita (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2025)
Financial management refers to an individual's ability to plan, organize, and manage financial resources effectively. Good financial literacy is essential for optimal financial management. Additionally, technological advancements have introduced financial technology (fintech), which facilitates financial transactions. This study aims to analyze the influence of financial literacy and fintech use on individual financial management among Vocational High School (SMK) students. This research employs a quantitative approach, using primary data collected through questionnaires distributed to 63 students of SMK Cendikia Paseh with a random sampling technique. Data analysis was conducted using SPSS software. The results indicate that financial literacy significantly influences financial management (t-value = 6.313 > 2.658857; significance = 0.000 < 0.05). However, fintech does not have a significant impact (t-value = -0.177 < 2.658857; significance = 0.860 > 0.05). Simultaneously, the F-test results (34.728 > 7.0771; significance = 0.000 < 0.05) confirm that financial literacy and fintech use together significantly influence financial management.